Tree shrew lavatories: a novel nitrogen sequestration strategy in a tropical pitcher plant - Charles, M Clarke; Ulrike, Bauer; C Lee, Ch'ien; Andrew, A Tuen; Katja, Rembold; Jonathan, A Moran (The Royal Society, 2009)
Nepenthes pitcher plants are typically carnivorous, producing pitchers with varying combinations of epicuticular wax crystals, viscoelastic fluids and slippery peristomes to trap arthropod prey, especially ants. However, ant densities are low in tropical montane habitats, thereby limiting the potential benefits of the carnivorous syndrome. Nepenthes lowii, a montane species from Borneo, produces two types of pitchers that differ greatly in form and function. Pitchers produced by immature plants conform to the ‘typical’ Nepenthes pattern, catching arthropod prey. However, pitchers produced by mature N. lowii plants lack the features associated with carnivory and are instead visited by tree shrews, which defaecate into them after feeding on exudates that accumulate on the pitcher lid. We tested the hypothesis that tree shrew faeces represent a significant nitrogen (N) source for N. lowii, finding that it accounts for between 57 and 100 per cent of foliar N in mature N. lowii plants. Thus, N. lowii employs a diversified N sequestration strategy, gaining access to a N source that is not available to sympatric congeners. The interaction between N. lowii and tree shrews appears to be a mutualism based on the exchange of food sources that are scarce in their montane habitat.